Size‐Dependent Enhancement of Electrocatalytic Oxygen‐Reduction and Hydrogen‐Evolution Performance of MoS2 Particles. Issue 36 (19th July 2013) - Wang, Tanyuan; Gao, Dongliang; Zhuo, Junqiao; Zhu, Zhiwei; Papakonstantinou, Pagona; Li, Yan; Li, Meixian
Abstract MoS2 particles with different size distributions were prepared by simple ultrasonication of bulk MoS2 followed by gradient centrifugation. Relative to the inert microscale MoS2, nanoscale MoS2 showed significantly improved catalytic activity toward the oxygen‐reduction reaction (ORR) and hydrogen‐evolution reaction (HER). The decrease in particle size was accompanied by an increase in catalytic activity. Particles with a size of around 2 nm exhibited the best dual ORR and HER performance with a four‐electron ORR process and an HER onset potential of −0.16 V versus the standard hydrogen electrode (SHE). This is the first investigation on the size‐dependent effect of the ORR activity of MoS2, and a four‐electron transfer route was found. The exposed abundant Mo edges of the MoS2 nanoparticles were proven to be responsible for the high ORR catalytic activity, whereas the origin of the improved HER activity of the nanoparticles was attributed to the plentiful exposed S edges. This newly discovered process provides a simple protocol to produce inexpensive highly active MoS2 catalysts that could easily be scaled up. Hence, it opens up possibilities for wide applications of MoS2 nanoparticles in the fields of energy conversion and storage.